MEMPERTIMBANGKAN NILAI ADIL DALAM WARISAN: Perspektif Naṣr Ḥāmid Abū Zayd - Muchlis, Ibnu (QOF, 2017)
Nasr Hamid Abu Zayd who has some thoughts related to the Qur’an is a contemporary Islamic critical thinker . He said that al Qur’an is a cultural product, this statement made him get under public criticism. However, besides that there are interesting things in the thought of Nasr Hamid Abu Zayd when discussing gender issues including in terms of division of inheritance which according to the author has not been known to the public. The idea that carried Nasr Hamid Abu Zayd is what the author needs to describe conceptually. Research on Gender Deconstruction Perspective Nasr Hamid Abu Zayd was done in order to answer: 1) How is the Qur’an according to Nasr Hamid Abu Zayd? 2) How is the legacy in the Qur’an according to Nasr Hamid Abu Zayd? This paper would like to reconstruct the thoughts of Nasr Hamid Abu Zayd on the Qur’an and the concept of justice in the inheritance. In order to reconstruct the thought of Nasr Hamid Abu Zayd, the author used theoretical hermeneutical of Schleirmacher’s. theory.